Pelatihan dan Pendampingan Optimasi Website Bagi Pengelola Desa Pulau Mubut - Yeni Rokhayati; Metta Santiputri; Sartikha Sartikha (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2022)
One of the promotional media of Mubut Island, that website, has been completed at the Batam State Polytechnic service activity in 2021. As a follow-up to this activity, the 2022 service needs to optimize the website promotion media which is also planned to be implemented in 2022. Because it will be the manager who will manage this website in the future, it is essential to train them so they can and are proficient in optimizing it. Website optimization will be done using Search Engine Optimization (SEO) techniques. First, the training will bring in an SEO practitioner. In addition, learning videos will also be made involving Project Based Learning (PBL) students. This learning media will also be given as an investment in knowledge in the future if something is forgotten. Website analytic data will be collected using the HiStats tool during this optimization. As an evaluation material for this service activity, the manager's ability to optimize the website will be reviewed by looking at the condition of the website after the training. In addition, it analyzes the improvement of website visitors before vs after optimization. The result is the website to be at the top of search engines, and the number of visitors to the Mubut Island tourist village website will increase significantly.